Option Value, Policy Uncertainty, and the Foreign Direct Investment Decision - Yu-Fu Chen; Michael Funke (Hamburg Institute of International Economics (HWWA), 2003)
In this paper we analyse the impact of policy uncertainty on foreign direct investment strategies. The paper follows the real options approach, which allows to investigate the value to a firm of waiting to invest and/or disinvest, when payoffs are stochastic due to political uncertainty and investments are partially reversible. Across the board we find that political uncertainty can be very detrimental to FDI decisions.
Keywords: F21; E22; D81; D92; 330; Real options; Investment; Foreign Direct Investment; Political Uncertainty; Direktinvestition; Betriebliche Investitionspolitik; Realoption; Politische Stabilität; Theorie